Sobre la tensión entre los fines del individuo y los de la sociedad - Mendoza Ibarra, Oscar Gibran (Universidad Michoacana de San Nicolás de Hidalgo, 2017)
The unstable relationship between individuals and society exists in many forms. In this case, when we refer to this relationship as one of tension, do this in view of I don't speak exclusively in the manner in which might oppose the first of the second, but the possibility of, without denying that opposition, discover that in different aspects these points can also match, derive from each other, influence each other, as well as feedback between them. Thus, complement each other without ceasing to be distinguished. Either isolated or associated individuals might want to consider various purposes (understood as those things which is intended to reach or achieve by means of actions), and is derived from the designated voltage, as the scope of these, you can find different oppositions in their way. The origin of this tension and opposition is located in the clash of wills and on the claim of a full exercise of the freedom by individuals, in which inevitably leads them into a cycle of disagreement, conflict, power and agreement. Finally, these elements combine to give form to the societies, and provide them with the features that distinguish from each other. And it is to the inside of the life in society, where we will live the constant struggle between individual and society, between the individual need for freedom and the social need for order, between morality repetitive and disruptive ethics, between competition and cooperation; and where the irony of finding the individual as a being as independent as a dependent is almost tangible. Throughout this thesis, is that we go into the analysis and reflection on many of the elements that surround this individuals and society relationship, and as trigger in the configuration of social order, including the establishment of the leadership of the association management that will give to the associated will be generated and the express way in which will define their aims as Association.

La relación inestable entre individuo-sociedad existe en muchas formas. En este caso, cuando nos referimos a esta relación como una de tensión, lo hacemos en vista de que no hablamos exclusivamente de la manera en que pueden llegar a oponerse el primero del segundo, sino a la posibilidad de, sin negar esa oposición, descubrir que en distintos puntos estas también pueden coincidir, derivar una de la otra, influenciarse mutuamente, así como retroalimentarse. Logrando así, complementarse sin dejar de distinguirse. Los individuos en forma aislada o asociada pueden plantearse distintos fines (entendidos como aquellas cosas a las cuales se pretende llegar o alcanzar por medio de acciones), y es derivado de la tensión señalada, que el alcance de estos, pueden encontrar distintas oposiciones en su camino. El origen de esta tensión y oposición, se encuentra en el choque de voluntades y en la pretensión de un ejercicio pleno de la libertad por parte de los individuos, misma que les lleva inevitablemente a adentrarse en un ciclo de desacuerdo, conflicto, poder y acuerdo. Finalmente, estos elementos se conjugan para darle forma a las sociedades, y dotarlas de las características que desigualan una de otra. Y es al interior de la vida en sociedad, en donde viviremos la constante lucha entre individuo y sociedad, entre la necesidad individual de libertad y la necesidad social de orden, entre la moral reiterativa y la ética disruptiva, entre la competencia y la cooperación; y en donde la ironía de encontrar al individuo como un ser tan independiente como dependiente es casi tangible. A lo largo de la presente tesis, es que nos adentraremos en el análisis y reflexión sobre muchos de los elementos que circundan esta relación individuo-sociedad y como desencadenan en la configuración del orden social, incluido el establecimiento del liderazgo de la asociación, el manejo que darán a la voluntad asociada que se genera, y la manera expresa en que definirán sus finalidades como asociación.
Facultad de Derecho y Ciencias Sociales. Maestría en Derecho
Keywords: info:eu-repo/classification/cti/5; FDCS-M-2017-1893; Ciencias políticas; Finalidad; Valor; Asociación; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/814